Vulvar and vaginal neoplasia in women with inflammatory bowel disease. Issue 2 (February 2020) - ,; Löwenberg, M.; Bodelier, A.; Verbeek, W.H.; Schoon, E.; Witteman, E.M.; Herwaarden, M.A.; Van Der Woude, C.J.; Lutgens, M.; Kouw, E.; Van Der Veek, P.J.; van der Hulst, R.W.; et al.
Abstract: Immunosuppressive drugs are the cornerstone in the treatment of inflammatory bowel disease (IBD), however they are associated with an increased risk of extra-intestinal cancer. Whether the risk for female genital tract malignancies, including vulvar and vaginal cancer, is increased is less clear. Our aim was to investigate the risk of these malignancies in IBD-patients. Histopathological data of all IBD patients with a vulvar or vaginal (pre-)cancerous lesion were retrieved from the Dutch nationwide network and registry of histopathology and cytopathology from 1991 to 2015. Medical history was retrieved from patient records. Data from the Central Office for Statistics, the Dutch comprehensive cancer organization, and the IBDSL cohort were obtained to calculate the standardized, and age-adjusted incidence rates. Fifty-five patients met the inclusion criteria. A standardized incidence rate of 1.2(95% CI:0.8–1.7) for vulvar and vaginal carcinoma among adult female IBD was calculated, which did not significantly differ from the general population. The use of immunosuppressive therapy did not increase the occurrence of vulvovaginal malignancy, nor did it influence the recurrence rate. However, immunosuppressive drugs ever-users were on average 11 years younger at the time of their gynaecological diagnosis. Overall, our data do not support intensified screening for vulvar or vaginal malignancies in female IBD patients.